Fe–Mn nanocomposites doped graphene quantum dots alleviate salt stress of Triticum aestivum through osmolyte accumulation and antioxidant defense - Md Salman Haydar; Salim Ali; Palash Mandal; Debadrita Roy; Mahendra Nath Roy; Sourav Kundu; Sudipta Kundu; Chandrani Choudhuri (Scientific Reports, 2023)
Abstract An investigation was carried out to evaluate the effect of graphene quantum dots (GQD) and its nanocomposites on germination, growth, biochemical, histological, and major ROS detoxifying antioxidant enzyme activities involved in salinity stress tolerance of wheat. Seedlings were grown on nutrient-free sand and treatment solutions were applied through solid matrix priming and by foliar spray. Control seedlings under salinity stress exhibited a reduction in photosynthetic pigment, sugar content, growth, increased electrolyte leakage, and lipid peroxidation, whereas iron-manganese nanocomposites doped GQD (FM_GQD) treated seedlings were well adapted and performed better compared to control. Enzymatic antioxidants like catalase, peroxidase, glutathione reductase and NADPH oxidase were noted to increase by 40.5, 103.2, 130.19, and 141.23% respectively by application of FM_GQD. Histological evidence confirmed a lower extent of lipid peroxidation and safeguarding the plasma membrane integrity through osmolyte accumulation and redox homeostasis. All of these interactive phenomena lead to an increment in wheat seedling growth by 28.06% through FM_GQD application. These findings highlight that micronutrient like iron, manganese doped GQD can be a promising nano-fertilizer for plant growth and this article will serve as a reference as it is the very first report regarding the ameliorative role of GQD in salt stress mitigation.